The impact of implicit and explicit corrective feedback in improving Malaysian ESL students’ L2 grammar in writing tasks - Sarmin Darshini, Mogan (2022)

(untitled)
In recent years, there has been much discussion about the value and impact of both explicit and implicit corrective feedback on second language writing. Researchers in second language writing are investigating whether written implicit corrective feedback aids in the acquisition of linguistic features. L2 writing researchers, on the other hand, generally focus on whether implicit and explicit corrective feedback tends to help 30 students enhance their composing texts and decrease language errors. Acknowledging these distinctions is critical because it informs English language writing educators about effective methods to provide feedback to student writers. Upper primary school students of in this research study received implicit and explicit corrective feedback as the students were divided into two groups. Participants were also interviewed to learn about their perspectives on teacher implicit written feedback and their reactions to it. The findings of this study indicated that teacher explicit corrective feedback assisted in the correction of certain grammatical errors, although the other group of errors necessitated the interference of teacher in giving implicit feedback.